Toll-like receptors 2 and 6 mediate apoptosis and inflammation in ischemic skeletal myotubes. (August 2019) - Patel, Hemanshu; Yong, Cissy; Navi, Ali; Shaw, Sidney G; Shiwen, Xu; Abraham, David; Baker, Daryll M; Tsui, Janice CS
Critical limb ischemia (CLI) is associated with skeletal muscle damage. However, the pathophysiology of the muscle damage is poorly understood. Toll-like receptors (TLR) have been attributed to play a role in ischemia-induced tissue damage but their role in skeletal muscle damage in CLI is unknown. TLR2 and TLR6 expression was found to be upregulated in skeletal muscle of patients with CLI. In vitro, ischemia led to upregulation of TLR2 and TLR6 by myotubes, and activation of the downstream TLR signaling pathway. Ischemia-induced activation of the TLR signaling pathway led to secretion of the pro-inflammatory cytokine interleukin-6 and muscle apoptosis, which were abrogated by neutralising TLR2 and TLR6 antibodies. Our study demonstrates that TLR2 and TLR6 are upregulated in ischemic muscle and play a role in ischemia-induced muscle damage. Thus, manipulating the TLR pathway locally may be of potential therapeutic benefit.